Nutritional Assessment in Patients with Double Malignant Obstruction: Biliary and Duodenal - Acharki, Mohamed; Boussenna, Imane; Khyat, Chaymaa; Kabbaj, Nawal; Bour, Abdellatif (Progress in Nutrition, 2026)
Background and aim: Biliary tract and pancreatic cancers carry a poor prognosis due to their rapid progression and frequent complications, such as malignant biliary and duodenal stenosis. The aim of this study was to evaluate the nutritional status of patients with simultaneous biliary and duodenal obstruction and its negative impact on their general condition and quality of life. Methods: This retrospective analysis included 200 patients hospitalized at Ibn Sina University Hospital in Rabat for malignant stenosis. Among them, 110 had isolated biliary stenosis (Group 1), while 90 presented with both biliary and duodenal stenosis (Group 2). Data collected included anthropometric measurements (weight, height, BMI), biological parameters (albumin, bilirubin, CRP), vomiting frequency, and Nutritional Risk Index (NRI). Results: The study population consisted of 54.5% men and 45.5% women, with a mean age of 56.7 years. Patients in Group 2 had significantly lower weight (47.4 ± 5.4 kg) and BMI (15.9 ± 2.0 kg/m²) compared with Group 1 (57.4 ± 9.3 kg and 20.0 ± 3.3 kg/m²; p = 0.000). Biologically, Group 2 showed more pronounced hypoalbuminemia (26.1 g/L vs 29.3 g/L) and higher bilirubin and CRP levels. Severe malnutrition was observed in 100% of Group 2 versus 76.3% of Group 1. Daily vomiting was also more frequent in Group 2 (84.4% vs 16.3%). Conclusions: These findings confirm the critical impact of double malignant obstruction on nutritional status and quality of life, underlining the importance of early nutritional assessment, timely intervention, and a multidisciplinary palliative approach to improve outcomes in this vulnerable population.